One‐Step Synthesis of Siloxanes from the Direct Process Disilane Residue. Issue 48 (14th October 2016) - Neumeyer, Felix; Auner, Norbert
Abstract: The well‐established Müller–Rochow Direct Process for the chloromethylsilane synthesis produces a disilane residue (DPR) consisting of compounds Me n Si2 Cl6− n ( n =1–6) in thousands of tons annually. Technologically, much effort is made to retransfer the disilanes into monosilanes suitable for introduction into the siloxane production chain for increase in economic value. Here, we report on a single step reaction to directly form cyclic, linear, and cage‐like siloxanes upon treatment of the DPR with a 5 m HCl in Et2 O solution at about 120 °C for 60 h. For simplification of the Si−Si bond cleavage and aiming on product selectivity the grade of methylation at the silicon backbone is increased to n ≥4. Moreover, the HCl/Et2 O reagent is also suitable to produce siloxanes from the corresponding monosilanes under comparable conditions. Abstract : Two birds with one stone : The disilane residue from the Müller–Rochow direct process undergoes cleavage and condensation to methylsiloxanes in a single step using HCl in Et2 O. Variation and optimization of reaction conditions lead to the selective formation of cyclic, linear, or cage‐like methylsiloxanes.